Clinical Outcome of Patients Hospitalized in a Tertiary Care Hospital of Nepal with Confirmed Influenza A/pdm 09(H1N1) in 2018/2019 - Acharya, Upasana; Acharya, Subhash Prasad (Journal of Nepal Health Research Council, 2020)
Background: It is important to monitor the cases affected by Influenza A/pdm09 as it is difficult to predict the behavior of Influenza A/pdm09 virus as a seasonal influenza. This study aimed to measure the clinical outcomes of patients with Influenza A/pdm 09 in a tertiary care hospital of Nepal in post pandemic period.Methods: A retrospective study was conducted in a tertiary care hospital of central Nepal to record the confirmed cases of Influenza A/pdm 09 from April 2018 to March 2019.The medical records of those patients whose throat sample had been sent to laboratory for testing Influenza A/pdm 09 were referred. The outcomes were then abstracted from the hospital system/medical record department.Results: Among 141 influenza suspected cases, 35.5%(N=50) were Influenza A/Pdm 09 positive. Both male and female were equal in distribution (N=25). Most positive cases were from the age group of 15-64 yrs. Out of total,72 %( N=36) with Influenza A/pdm 09 were discharged after treatment whereas case fatality rate was 22 %( N=11). Twenty-one positive cases were admitted in intensive care unit in which 52.4% expired. The average length of stay in I.C.U and mechanical ventilation were 6.4 days and 5.8 days respectively.Conclusions: This study in post pandemic period in Nepal shows the outcomes of patients with confirmed influenza A/pdm 09 in a year time period with comparably high case fatality rate. Keywords: Influenza A/pdm 09; Nepal; post pandemic, retrospective